CONTENTS OF IMPROVING THE METHODOLOGICAL TRAINING OF A FUTURE TECHNOLOGY EDUCATION TEACHER BASED ON AN INNOVATIVE APPROACH - Z. U. Dzhumagulov (American Journals, 2023)
This article is devoted to the improvement of the methodology of developing the methodical training of future technology teachers based on an innovative approach.
Keywords: Innovative pedagogical processes, educational process, knowledge, formation, creative action